2017
DOI: 10.1158/2159-8290.cd-17-0057
|View full text |Cite
|
Sign up to set email alerts
|

Gatekeeper Mutations and Intratumoral Heterogeneity inFGFR2-Translocated Cholangiocarcinoma

Abstract: genetic translocations are frequent in cholangiocarcinoma, yet despite initial sensitivity to FGFR inhibitors in clinic, patients quickly become resistant to targeted therapies. The work published by Goyal and colleagues demonstrates that acquisition of gatekeeper mutations in and intratumoral heterogeneity drive resistance in patients with-translocated intrahepatic cholangiocarcinoma, which will have important implications for management of the disease in clinic. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…FGFRs represent tyrosine kinase receptors, with FGFR2 being involved in the upregulation of RAS, JAK, and PI3K/mTOR pathways; thus, FGFR2 aberrations play a role in modifying processes of cellular migration, angiogenesis, proliferation, and survival [ 43 , 44 ]. In the last decade, a wide number of agents targeting FGFR isoforms have been investigated in iCCA patients, such as infigratinib, pemigatinib, derazantinib, erdafitinib and, more recently, futibatinib ( Table 1 ) [ 45 , 46 ].…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…FGFRs represent tyrosine kinase receptors, with FGFR2 being involved in the upregulation of RAS, JAK, and PI3K/mTOR pathways; thus, FGFR2 aberrations play a role in modifying processes of cellular migration, angiogenesis, proliferation, and survival [ 43 , 44 ]. In the last decade, a wide number of agents targeting FGFR isoforms have been investigated in iCCA patients, such as infigratinib, pemigatinib, derazantinib, erdafitinib and, more recently, futibatinib ( Table 1 ) [ 45 , 46 ].…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…The first evidence of FGFR2 fusions in iCCA patients was reported by Wu and colleagues in 2013 [ 53 ]; subsequently, an impressive number of studies have been published on this topic, also observing that etiology and geographical elements could modify the prevalence of FGFR aberrations in CCA. Recent years have registered the advent of several different methods able to identify FGFR2 fusions, including traditional immunohistochemistry, polymerase chain reaction (PCR), fluorescent in situ hybridization (FISH), and other approaches based on NGS [ 56 ]. Nonetheless, these methods are not superimposable since they have been associated with considerable differences in terms of comparability, reproducibility and specificity.…”
Section: Fgfr Aberrations In Cholangiocarcinomamentioning
confidence: 99%
“… 50 Acquired resistance is often linked to tumor heterogeneity and the occurrence of secondary mutations in the FGFR2 kinase domain. 84 This phenomenon can be regarded as the stress response of cancer cells to therapeutic drugs. Recently, Krook et al reported a patient with metastatic cholangiocarcinoma and altered FGFR2 who was enrolled in a phase II clinical trial of the FGFR inhibitor BGJ398.…”
Section: Fgfr Targeted Therapy For Iccamentioning
confidence: 99%